Use of vector control to protect people from sleeping sickness in the focus of Bonon (Côte d'Ivoire). - Dramane Kaba; Vincent Djohan; Djakaridja Berté; Bi Tra Dieudonné Ta; Richard Selby; Koffi Alain De Marie Kouadio; Bamoro Coulibaly; Gabehonron Traoré; Jean-Baptiste Rayaisse; Pierre Fauret; Vincent Jamonneau; Kouakou Lingue; et al. (Public Library of Science (PLoS), 2021)
Background Gambian human African trypanosomiasis (gHAT) is a neglected tropical disease caused by Trypanosoma brucei gambiense transmitted by tsetse flies (Glossina). In Côte d'Ivoire, Bonon is the most important focus of gHAT, with 325 cases diagnosed from 2000 to 2015 and efforts against gHAT have relied largely on mass screening and treatment of human cases. We assessed whether the addition of tsetse control by deploying Tiny Targets offers benefit to sole reliance on the screen-and-treat strategy. Methodology and principal findings In 2015, we performed a census of the human population of the Bonon focus, followed by an exhaustive entomological survey at 278 sites. After a public sensitization campaign, ~2000 Tiny Targets were deployed across an area of 130 km2 in February of 2016, deployment was repeated annually in the same month of 2017 and 2018. The intervention's impact on tsetse was evaluated using a network of 30 traps which were operated for 48 hours at three-month intervals from March 2016 to December 2018. A second comprehensive entomological survey was performed in December 2018 with traps deployed at 274 of the sites used in 2015. Sub-samples of tsetse were dissected and examined microscopically for presence of trypanosomes. The census recorded 26,697 inhabitants residing in 331 settlements. Prior to the deployment of targets, the mean catch of tsetse from the 30 monitoring traps was 12.75 tsetse/trap (5.047-32.203, 95%CI), i.e. 6.4 tsetse/trap/day. Following the deployment of Tiny Targets, mean catches ranged between 0.06 (0.016-0.260, 95%CI) and 0.55 (0.166-1.794, 95%CI) tsetse/trap, i.e. 0.03-0.28 tsetse/trap/day. During the final extensive survey performed in December 2018, 52 tsetse were caught compared to 1,909 in 2015, with 11.6% (5/43) and 23.1% (101/437) infected with Trypanosoma respectively. Conclusions The annual deployment of Tiny Targets in the gHAT focus of Bonon reduced the density of Glossina palpalis palpalis by >95%. Tiny Targets offer a powerful addition to current strategies towards eliminating gHAT from Côte d'Ivoire.